Effective Communication Techniques in Conveying Religious Values Through Animated Films (Study at Al Marjan Elementary School, Bengkulu City) - Anisa Dwi Saputri; Anis Endang; Bayu Risdiyanto (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2023)
This research purpose is to describe dffective communication in delivering religious values with Animated movie. This research is gwantitative research and data are collected by using observation. interview and documentation. The result of this research shows hat efective communication technigues which used by teachers at SD AL MARJAN Bengkulu city in delivering religious values by building eredibiliay On students by creating learning system becomes fa, such as Watch Upin and Ipin movie together. Teachers tricd to obtain students" ust and with hat trust, it made teacher able to deliver the religious values material. Writer saw that religion teachers have selfcreativeness during teaching. When delivering religious values wilh Upin and Ipin animation, teachers used several ace expression and gestures s0 ihe delivery became. more interesting and eomicted. By having his attraction, students will be interested in paying attention 40 what Ihe teacher is saying. When Ihe teacher explains Ihe material. Especially religious values, the teacher already understands what the students are like, the teacher is able to listen 10 what the students say, not only listening but aho responding, paying aitention 10 students, s0 that students become clase and familiar. Afier finishing delivering the material he students seemed very enihusiastic and asked some guestions 10 Ihe teacher, and the teacher responded. very well s0 hat there was a discussion. teachers and students use language that is easy t0 understand, ihis makes ihe atmosphere 0f communication come alive, and ihe message conveyed can be well received. Upin Ipin animated movie was Ehasen for reasons acconding 10 Ihe age af Ihe students, it is still very popular with students, easy 10 understand and in accordance with Ihe material to be delivered by the teacher. The teacher can accept the student situation, accept all the different habits and character of students.